2000
DOI: 10.3122/15572625-13-2-116
|View full text |Cite
|
Sign up to set email alerts
|

Managing The Nondeflating Urethral Catheter

Abstract: Background: Urethral catheterization is a routinely perfonned procedure in hospitalized patients. Numerous complications have been reported secondary to urethral catheter placement.Methods: The medical literature was searched using the following key words: "urethral catheter," "complications," and "management." A case report is described and a review of the literature is provided to assist in managing the nondetlating urethral catheter balloon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 11 publications
1
20
0
5
Order By: Relevance
“…Shapiro et al presented a management algorithm for RFC. His observation was similar to those made in this study [7]. Hollingsworth et al found that 31% of his patients needed cutting of the side port to deflate the balloon while in 15% guide-wire had to be inserted.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Shapiro et al presented a management algorithm for RFC. His observation was similar to those made in this study [7]. Hollingsworth et al found that 31% of his patients needed cutting of the side port to deflate the balloon while in 15% guide-wire had to be inserted.…”
Section: Discussionsupporting
confidence: 75%
“…Among all the chemicals used for this purpose, mineral oil has been found to cause the least damage to the bladder [11]. If urine is present in the bladder when chemicals are used, chemicals get diluted and this lessens their concentration leading to lessened chances of bladder damage [7]. Although we used mineral oil successfully in just one patient, he had hematuria for two days which resolved on conservative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of them has advantages and disadvantages (2,4). The dissolution of the ball wall with chemical substances (3a) includes various substances such as ether, chloroform, benzene, acetone and mineral oil (2,3,4,5). Although it is a quick and effective system to break the globe, it presents some serious inconveniences.…”
Section: Acting Protocolmentioning
confidence: 99%
“…When this technique is not effective, it is necessary to resort to maneuvers that involve the rupture of the ball for which there are several options that we have to summarize into 3 groups (Fig 3 Step 3): Chemical dissolution (3a), ball puncture (3b) and hyper filling (3c). Each of them has advantages and disadvantages (2,4). The dissolution of the ball wall with chemical substances (3a) includes various substances such as ether, chloroform, benzene, acetone and mineral oil (2,3,4,5).…”
Section: Acting Protocolmentioning
confidence: 99%